Multicystic Dysplastic Kidney: What Changed in Three Decades? - Mota Almeida Magalhães, Diana Raquel (2024)
Introduction: Multicystic dysplastic kidney (MCDK) is a severe form of cystic renal dysplasia that typically exhibits a favorable natural history. Though complications are low, systematic follow‐up is needed. Methods: Retrospective analysis covering children diagnosed with MCDK, undergoing follow‐up in a tertiary pediatric nephrology unit, from January/2011‐December/2023. Variables assessed included demographics, diagnosis details, evolution and treatment. A comparison with prior studies (1989‐2000 and 2000‐2010) was also conducted. Results: Were included 53 children, most with prenatal diagnosis. Left kidney was most often involved, and additional kidney abnormalities were present in 39.6%. Ultrasound was conducted in all patients, and at least one nuclear med‐ icine test was conducted in 94.3%. Involution of the affected kidney occurred in 96.2%, with complete involution in 49.1%. Complications, including urinary tract infections, were reported in 34.0%. Compared with the previous study periods, the latest period was notable for higher percentage of prenatal diagnosis, fewer voiding cystourethrographies and nephrectomies performed, and higher percentage of contralateral anomalies and complications. Discussion: MCKD was predominantly diagnosed prenatally. The incidence of associated anomalies aligns with previous findings. Antenatal ultrasonography is the diagnostic method of choice. Our study demonstrated the typical natural his‐ tory of the disease, with high partial and complete involution rates. Management trends shifted from surgery to conser‐ vative approaches, reflecting the improved understanding of MCDK’s favorable prognosis. Long‐term follow‐up, typically less invasive in recent years, remains crucial especially for patients with contralateral abnormalities, emphasizing serial ultrasonographic evaluation, and frequent monitoring of blood pressure, proteinuria and kidney function markers.